Flame retardant properties of the bark powder of Anadenanthera peregrina var. falcata (Benth.) Altschul (angico) studied by coupled thermogravimetry-Fourier transform infrared spectroscopy - Souza, Aguinaldo Robinson de [UNESP]; Cavassan, Osmar [UNESP]; Almeida, M. V. de [UNESP]; Legendre, Alexandre de Oliveira [UNESP]; Bannach, Gilbert [UNESP] (Elsevier B.V., 2014)
In this research, the bark powder of Anadenanthera peregrina var. falcata (angico) was characterized by means of simultaneous thermogravimetry-differential scanning calorimetry (TG-DSC) and differential scanning calorimetry (DSC) in order to investigate the chemical features responsible for the flame retardant properties of this plant. The TG-DSC and DSC data evidenced that dehydration occurs between 40 and 140 degrees C and that the anhydrous solid is stable up to 195 degrees C, when thermal decomposition begins. Coupled thermogravimetry-Fourier transform infrared spectroscopy (TG-FTIR) techniques were used to identify the volatile products evolved during the decomposition of the sample, showing that water and carbon dioxide are the majority products formed by its decomposition even at temperatures as low as 200 degrees C. The strong endothermic peak associated with the release of water provides a reasonable explanation for the fire retardant properties of angico. (C)2013 Elsevier B.V. All rights reserved.
Keywords: Anadenanthera peregrina var.falcata; Thermal behavior; Coupled thermogravimetry-infrared; spectroscopy